Answer of article’s authors «Peculiarities of surgical correction of different forms hand syndactylly in children. Retrospective study of own experience» - Harbuzniak, I. M.; Hrytsenko , A. M. (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Answer of article’s authors «Peculiarities of surgical correction of different forms hand syndactylly in children. Retrospective study of own experience»